Greenhouse gas emission and carbon leaching in pineapple cultivation on tropical peat soil - Haruna, Ahmed Osumanu; Lim, Liza Nuriati Kim Choo (Universiti Putra Malaysia Press, 2015)
This book contains information on greenhouse gas emission and leaching of carbon in pineapple (Ananas comosus (L.) Merr.) cultivation on tropical peat soils. It discusses partitioning of carbon dioxide, methane, and nitrous oxide from cultivated tropical peats into: (a) total respiration from root respiration, microbial respiration, and peat decomposition, (b) microbial respiration, and peat decomposition, and (c) peat physical oxidation due to shrinkage and consolidation. It further discusses partitioning of carbon (dissolved organic carbon) in water that is normally leached from cultivated tropical peats. Therefore, the book is designed as a quick reference text that will enable farmers, students, and scientists to have an idea about greenhouse gas emissions from cultivated peats. This book will also be of significant interest to those working in the applied sciences.